2000
DOI: 10.1080/18811248.2000.9714942
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Precipitated Hydride on the Fracture Behavior of Zircaloy Fuel Cladding Tube

Abstract: In order to clarify the influence of precipitated hydride on the fracture behavior of Zircaloy cladding tubes, the stress-strain distribution of the cladding was estimated by finite element method (FEM) analysis. The mechanical properties of ex-phase of zirconium and zirconium hydride required for the analysis were examined by means of an ultrasonic pulse-echo method and a tensile test. It was found from the analysis that the nonhydrided cladding has the highest equivalent plastic strain at the inner surface o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Through-thickness crack propagation and fracture toughness of hydrided zirconium alloys was previously analyzed at 25°C, 300°C, 375°C by Dubey et al (1999), Kuroda et al (2000), Pierron et al (2003), Glendening et al (2004), Desquines et al (2005), Bertolino et al (2006), Tomiyasu et al (2007), Daum et al (2007), Georgenthum et al (2008), Udagawa et al (2009), Sartoris et al (2010, Hsu et al (2011), Raynaud et al (2012. It appears in these studies that hydrogen content and hydride orientation are key parameters to assess zirconium alloys fracture toughness at room temperature.…”
Section: Introductionmentioning
confidence: 97%
“…Through-thickness crack propagation and fracture toughness of hydrided zirconium alloys was previously analyzed at 25°C, 300°C, 375°C by Dubey et al (1999), Kuroda et al (2000), Pierron et al (2003), Glendening et al (2004), Desquines et al (2005), Bertolino et al (2006), Tomiyasu et al (2007), Daum et al (2007), Georgenthum et al (2008), Udagawa et al (2009), Sartoris et al (2010, Hsu et al (2011), Raynaud et al (2012. It appears in these studies that hydrogen content and hydride orientation are key parameters to assess zirconium alloys fracture toughness at room temperature.…”
Section: Introductionmentioning
confidence: 97%
“…4,5) The experiments by Kuroda et al also support this assumption: the failure stress of hydride was evaluated to be only about 18 MPa. 6) In addition, Tomiyasu et al conducted RIA simulation experiments at the NSRR with unirradiated prehydrided cladding and successfully reproduced PCMI failure as were observed in high-burnup fuels. These experiments have clearly demonstrated that hydride clusters play the most important role in PCMI failure during an RIA.…”
Section: Introductionmentioning
confidence: 78%
“…The effect of local hydride precipitation on the mechanical properties of the matrix has attracted attention [ 147 ]. Mechanical tests, such as the Expansion Due to Compression test, and tensile tests were conducted on samples containing localized hydride and demonstrated that hydride blisters and hydride rims have no deformation capacity, even at 480 °C [ 148 , 149 , 150 , 151 , 152 ]. Notably, the reduction in the strength and plasticity of the matrix is proportional to the depth of the bister/rim.…”
Section: Hydride-induced Embrittlementmentioning
confidence: 99%